Some questions of world economic competition - Simon György; Simon György Jr. (Međunarodni Problemi, 2008)
The paper searches for an answer to the following questions: why had the situation in Japan and the European Union situation improved in comparison with the one in United States prior to the first oil price shock; what factors altered this tendency later, especially from the 1990s onwards; what was the role of the international economic conditions in all that? Applying the models of mathematical economics, the authors have proven their main statements by an econometric investigation. The most important conclusion that can be drawn is that in the world economic competition the situation both in Japan and the European Union was primarily determined by the changes in the world economic conditions, chiefly the oil prices in the world market and the exchange rates, what can less be said of the United States.